EVALUASI KINERJA BADAN LINGKUNGAN HIDUP DALAM UJI EMISI GAS BUANGAN KENDARAAN BERMOTOR DI KOTA PEKANBARU - Putri Insyira; Tuti Khairani Harahap (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The Environmental Agency is an institution for the technical area of technical is on element of supporting the mayor in charge of carrying out the preparation and implementation of policy are as that is specific, in terms of this policy enviromental. The Enviromental Agency always organizes vehicle’s emission once a year. The proposed to keep air quality in Pekanbaru and to know how many percents vehicle’s emission effect for air pollution in Pekanbaru. So, many things are valued from perfomance evaluation of environment agency in Pekanbaru to know about The Environmental Agency to reach the goal of vehicle’s emission program. The goal is knowing about The Environmental agency’s perfomance and the factors those effect for vehicle’s emission in Pekanbaru.The concept of theory that researchers is perfomance, evaluation and organization. The researchers uses kualitatif method with descriptive review. In data collections are using interview technic, observation, documentation and library list.The result of this research is showing that The Environmental Agency’s perfomance in vehicle’s emission runs well in Pekanbaru, because all of vehicle’s emission programs match with Standard Operating Procedure (SOP). Responsivity, Reponbility, and Accountability of The Environmental Agency’s perfomance. Factors of perfomance effect is human resouces, facilities and infrastructure, cooperative, local goverment regulations, and public participationKey words : Evaluation, Perfomance, Vehicle’s Emissions